PENGEMBANGAN MODEL MATEMATIS PENGARUH CUSTOMER SEGMENT DAN VALUE PROPOSITION PADA KESUKSESAN PRODUK - Trisna, Arie ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Defining customer segment is one of the most critical factor to perform business model. A firm has to be able to define the most prospective customer segment in order to innovate the suitable value proposition. However, each different customer segment has its own significant preference and satisfaction on value propositions. This research aimed to develop mathematical model to predict the rank of product success based on value propositions and customer segment both high-end segment and low-end segment. Mathematical models were formulate by 80% data of each segment using Kano model. Meanwhile, 20% of data is used to examine the accuracy of the models. In order to assist product developer, tool is developed by using pairwise comparison as an input of the product value proposition and it has been tested by 17 users. This research has developed mathematical models that are able to predict 54,17% high end segment rank and 67% low end segment rank. In order to gain the efficiency of the computation time, the mathematical models are used to formulate the tool to predict the rank of product. Pairwise comparison is used to help the user examine each value proposition of the product. Tool is able to predict with 2% lower than mathematical model prediction of high-end segment on selected type of product, while 9% lower than mathematical model prediction rank of low-end segment. There are 5 value propositions that able to fulfill high-end segment requirement, namely, authenticity and value, design and experience, innovation and leadership, marketing, communication and leadership, and sustainability and simplicity. Price, feature, safety, product performance, after sales service, economical consumption, convenience, ordering ease, extra feature, brand, design, and advertising are value propositions that contribute to low-end segment satisfaction.